Implikasi Yuridis Undang-Undang Nomor 28 Tahun 2004 Terkait Penyesuaian Anggaran Dasar Yayasan - Kartikawati, Ayu; Widhiyanti, Hanif Nur (Jurnal Ilmiah Pendidikan Pancasila dan Kewarganegaraan, 2021)
This study aimed to adjust the statute for foundations established before the enactment of Law Number 28 of 2004 and analyze the legal consequences for foundations established before the enactment of Law Number 28 of 2004 that did not make adjustments to the articles of association. This study used a normative juridical method with a statutory and case approach. The results showed that the purpose of adjusting the articles of association for foundations that were established before the enactment of Law Number 28 of 2004 was to obtain recognition as a foundation, either technically or administratively. The legal consequences for foundations that were established before the enactment of Law Number 28 of 2004 that did not make adjustments to the statute were in the form of losses due to loss of previous history and wealth in the form of assets that had been obtained by the foundation so that the foundation became like a new foundation.